2001
DOI: 10.1098/rstb.2001.0959
|View full text |Cite
|
Sign up to set email alerts
|

Complex bird clocks

Abstract: The circadian pacemaking system of birds comprises three major components: (i) the pineal gland, which rhythmically synthesizes and secretes melatonin; (ii) a hypothalamic region, possibly equivalent to the mammalian suprachiasmatic nuclei; and (iii) the retinae of the eyes. These components jointly interact, stabilize and amplify each other to produce a highly self-sustained circadian output. Their relative contribution to overt rhythmicity appears to differ between species and the system may change its prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 63 publications
3
65
0
1
Order By: Relevance
“…These results indicate that the elimination of the pineal melatonin rhythm, or a reduction of its amplitude, renders the circadian pacemaker a less self-sustained, often highly damped, oscillatory system. By and large, these effects are consistent with predictions derived from oscillator theory (see especially Aschoff 1981;Gwinner et al 1997;Gwinner and Brandstätter 2001), which predicts that a reduction of the degree of selfsustainment of a rhythm should not only increase the range of entrainment but also shorten the resynchronization times following phase-shifts of the zeitgeber. This hypothesis has not yet been directly tested.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…These results indicate that the elimination of the pineal melatonin rhythm, or a reduction of its amplitude, renders the circadian pacemaker a less self-sustained, often highly damped, oscillatory system. By and large, these effects are consistent with predictions derived from oscillator theory (see especially Aschoff 1981;Gwinner et al 1997;Gwinner and Brandstätter 2001), which predicts that a reduction of the degree of selfsustainment of a rhythm should not only increase the range of entrainment but also shorten the resynchronization times following phase-shifts of the zeitgeber. This hypothesis has not yet been directly tested.…”
Section: Introductionsupporting
confidence: 86%
“…The pineal organ and its daily periodic secretion of melatonin are an important component of avian circadian pacemaking systems (Kumar 2001;Gwinner and Brandstätter 2001;Kumar et al 2004). In vitro studies have revealed that avian pineal organs are by themselves capable of circadian melatonin production and secretion (Takahashi et al 1980;Brandstätter et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, conversely to mammals, where the pineal gland has a merely secretory role, but it is not photosensitive, the avian pineal contains its own photoreceptor, pinopsin (P opsin), with a spectral peak between 460 and 470 nm (Max et al 1995 ). Because of its intrinsic sensitivity to light, the pineal gland plays a pivotal role in the regulation of avian circadian rhythms (Gwinner and Brandstätter 2001 ).…”
Section: Avian Photoreceptionmentioning
confidence: 99%
“…In mammals, the master circadian clock is located in a specific set of cells of the hypothalamus, the suprachiasmatic nuclei (SCN) (Menaker et al 1997 ), which receives light stimuli from a subset of ganglion cells called ipRGCs (see above) (Berson et al 2002 ), while the pineal gland is less involved in circadian timing. In birds, non visual light stimuli are mainly received in the retina, the hypothalamus (via the retinal hypothalamic tract, RHT), and in the pineal gland (Gwinner and Brandstätter 2001 ). At present, it is still unclear how this information is integrated between the different components of the avian central circadian system (Cassone 2013 ), but it is evident that the pineal gland plays a much bigger role than it does in mammals.…”
Section: Light and Circadian Rhythmsmentioning
confidence: 99%